(76-6)=3x

Simple and best practice solution for (76-6)=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (76-6)=3x equation:



(76-6)=3x
We move all terms to the left:
(76-6)-(3x)=0
We add all the numbers together, and all the variables
-3x+70=0
We move all terms containing x to the left, all other terms to the right
-3x=-70
x=-70/-3
x=23+1/3

See similar equations:

| p=2(20)+2(14) | | F(d)=110+0,12d | | y+1/3=2/7 | | -5(5x+2)-x+2=−5(5x+2)−x+2=-86 | | -n=28=n | | −3|2x−1|=−15 | | 8-5t=4+10(7-2t) | | k+12=36 | | 424=-8(6n-5) | | 17-y=10 | | 2+-8=-1x | | 1/3x+1/9=8 | | b/8+2=10 | | 2x+2*5x=48 | | 8/b+2=10 | | 3|2x-1|+14=8 | | 3x-5=-36x-4 | | 4x+2(x-5)=3(2x-4 | | 4.6y-(2y-5)=29 | | .x−6=8 | | y/3+10=40 | | 9+6m=8(10-2m) | | y/3+10=41 | | 4(7+6n)=-164 | | .x+8=6 | | 6k+12=6(k+2) | | -31=3w=9=8w | | (3.50+3.50)v=41 | | 6(4x-7)=-2(2x+5) | | 3x-5=-12(3x-(1/3)) | | (15/x+5)=4(-3x/x+5) | | 3-3(8m-4)=25-4m |

Equations solver categories